2020
DOI: 10.1080/03602532.2020.1832112
|View full text |Cite
|
Sign up to set email alerts
|

The development and hepatotoxicity of acetaminophen: reviewing over a century of progress

Abstract: Acetaminophen (APAP) was first synthesized in the 1800s, and came on the market approximately 65 years ago. Since then, it has become one of the most used drugs in the world. However, it is also a major cause of acute liver failure. Early investigations of the mechanisms of toxicity revealed that cytochrome P450 enzymes catalyze formation of a reactive metabolite in the liver that depletes glutathione and covalently binds to proteins. That work led to the introduction of N acetylcysteine (NAC) as an antidote f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 236 publications
(279 reference statements)
0
36
0
Order By: Relevance
“…Almost all RCTs and meta-analyses reported numbers of adverse events from paracetamol that were inferior to those of NSAIDs and comparable to those of placebo. However, reviews on long-term observational data reported increased cardiovascular, gastrointestinal, and renal adverse events during therapy with paracetamol, especially in the high dose range; cases of acute liver failure have been reported after accidental and unintentional overdose of paracetamol [ 10 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 ]. Acute liver failure is infrequent with an approximate incidence for all causes of 1/million/year and is declining [ 134 ].…”
Section: Safety and Toxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…Almost all RCTs and meta-analyses reported numbers of adverse events from paracetamol that were inferior to those of NSAIDs and comparable to those of placebo. However, reviews on long-term observational data reported increased cardiovascular, gastrointestinal, and renal adverse events during therapy with paracetamol, especially in the high dose range; cases of acute liver failure have been reported after accidental and unintentional overdose of paracetamol [ 10 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 ]. Acute liver failure is infrequent with an approximate incidence for all causes of 1/million/year and is declining [ 134 ].…”
Section: Safety and Toxicitymentioning
confidence: 99%
“…Paracetamol overdose can cause liver damage and failure for which different mechanisms have been suggested [ 136 , 137 , 138 ]. At therapeutic doses, paracetamol is metabolized in the liver primarily by glucuronidation (50–60%) and sulfonation pathways (25–30%) and less by oxidation by cytochrome P450 2E1 (<10%).…”
Section: Safety and Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of mitochondria triggers an oxidative stress cascade that leads to accumulation of reactive oxygen species, formation of peroxynitrite, mitochondrial membrane permeability transition, and ultimately cell death [22]. Acute paracetamol toxicity may be antagonized by restoration of GSH stores via early administration of high-dose Nacetyl-cysteine administration [23]. At a later stage, moderate hypothermia to induce RNA-binding motif protein 3 [24] appears to be a promising strategy that is awaiting clinical evaluation.…”
Section: Pharmacokinetics and Toxicologymentioning
confidence: 99%
“…Conversion of APAP to the reactive metabolite N-acetyl- p -benzo quinoneimine (NAPQI) initiates the hepatotoxicity. NAPQI binds to free sulfhydryl groups on amino acid residues, depleting hepatic glutathione and damaging proteins (Jollow et al, 1973; Mitchell et al, 1973; McGill and Hinson, 2020). The protein binding leads to mitochondrial dysfunction and oxidative stress (Jaeschke, 1990; Cover et al, 2005), which activates the c-Jun N-terminal kinases 1/2 (JNK) and other kinases (Gunawan et al, 2006; Hanawa et al, 2008; Nakagawa et al, 2008; Ramachandran et al, 2013).…”
Section: Introductionmentioning
confidence: 99%